The Role of the Department of Public Relations at Yarmouk University in Limiting the Spread of Rumor in Times of Crisis - Olaimat , Farhan; Maabreh, Aseel (Jordan Journal of Social Sciences, 2024)
This study aimed to identify the role of the Department of Public Relations (DPR) at Yarmouk University in limiting the spread of rumors in times of crises from the viewpoint of students of the department, by conducting a descriptive study using the survey method for an intentional sample of (321) male and female students from the DPR. The findings of the study revealed that the most important role of the DPR at Yarmouk University in curbing rumors in times of crises is that it relies on the various media to communicate facts about the crisis to prevent rumors from happening. In addition, the findings show that electronic messages are the most important means of communication used by the DPR to reduce rumours. Further, the researchers found that the most important factor in the spread and circulation of rumors is the recipient's indifference to the truth or his/her lack of search for it. Finally, there are no statistically significant differences between the average answers of the students of the Public Relations Department / College of Media at Yarmouk University towards the role of the Public Relations Department in limiting the spread of rumor in crises according to the gender, age, and school year variables.